Novel design and analysis of RF MEMS shunt capacitive switch for radar and satellite communications - Maham Kamil Naji; Alaa Desher Farhood; Adnan Hussein Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, a new type of Radio Frequency Micro-Electro-Mechanical System (RF-MEMS) shunt capacitive switch is designed and studied. RF MEMS switch has a number of advantages in a modern telecommunication system such as low power consumption, easy to fabricate and power handling capacity at radio frequency. At high frequency applications, this switch shows very superior performance due to which it now became one of the key elements for RF application. In this proposed design, an innovative type of MEMS switch is designed. The MEMS switch structure consists of substrate, co-planar waveguide (CPW), dielectric material and a metallic bridge. The proposed MEMS switch has a dimension of 508 µm × 620 µm with a height of 500 µm. The substrate used is GaAs material. The relative permittivity of the substrate is 12.9. This proposed MEMS switch is designed and simulated in both UP (ON) state and DOWN (OFF) state. The proposed RF-MEMS switch is designed and simulated using Ansoft High frequency structure simulator (HFSS) electromagnetic simulator. The simulated result shows better performance parameters such as return loss ( <-10 dB)  and insertion loss ( > -0.5 dB) in UP state, whereas return loss ( > -0.5 dB) and isolation (<-10 dB) in DOWN state. This switch has good isolation characteristics of – 43 dB at 27 GHz frequency.